Analysis of the references of the nursing diagnoses Impaired Walking (00088) - Marques-Vieira, Cristina (2014)
Introduction: The concept analysis is an important research method for the development of the nursing knowledge and it is suggested to be the first phase of the nursing diagnoses validation(1). The taxonomy II of NANDA-I integrates nursing diagnoses based on analysis and development of the concept, as well as label, defining characteristics, related factors and references(2). Objective: Characterize the attributes, related concepts and clinical indicators from the references of the nursing diagnosis impaired walking. Materials and methods: Analisys the concept impaired walking, according to Rodgers, among the 3 references of the nursing diagnosis from the last edition(2). Results: The references were published between 1988 and 2004 and they not refer to validation studies. The attributes are: checked the sensitivity of the neuromuscular findings with performance four routine mobility maneuvers: getting up from a chair, sitting down, turning while walking, and raising the feet while walking(3), decreased force production, less motion and force, decreased gait speed(4), fear of falling, curtail in activities, walk speed and distance(5). The related concept are: although hip and knee flexion(3), impaired mobility, impairment in proprioceptive and vibratory sensory system, impaired gait and balance, vestibular changes(4), environment hazard, fall history, lower balance, activity reduction, weight shifting ability, poor physical performance, global weakness, limits of stability (reduction) and lower limb weakness(5). The clinical indicators are: getting up from a chair, sitting down, turning while walking, and raising the feet while walking; the sensory and neuromuscular examination (vision, hearing, frontal reflexes, position sense, tone, coordination, and manual muscle testing)(3); impairment in proprioceptive and vibratory sensory systems; impaired balance, and vestibular changes; pharmaceutical variables; depression and impaired cognition(4), limits of stability, walking speed and lower extremity muscle strength(5). Conclusion: The results are similar to the elements of the diagnosis at the taxonomy II, but since the most recent reference is from 2004 it is desirable to develop clinical validation to contribute to the taxonomy improvement.